2016
DOI: 10.1039/c6cp02198k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical interfacial influences on deoxygenation and hydrogenation reactions in CO reduction on a Cu(100) surface

Abstract: a Electroreduction of CO2 to hydrocarbons on copper surface has attracted much attention in the last decades for providing a sustainable way for energy store. During the CO2 and further CO electroreduction processes, the deoxygenation that is C-O bond dissociation, and hydrogenation that is C-H bond formation, are two main types of surface reactions catalyzed by copper electrode. In this work, by performing the state-of-the-art constrained ab initio molecular dynamics simulations, we have systematically invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…From the simulations performed in an aqueous interfacial model with explicit water molecules, we may learn a great deal about electrocatalysis at the atomic scale than without them. [25][26][27][28][29][30][31][32][33] Some results have shown that the presence of aqueous solution has a great impact on mechanisms and energetics of surface reactions.…”
mentioning
confidence: 99%
“…From the simulations performed in an aqueous interfacial model with explicit water molecules, we may learn a great deal about electrocatalysis at the atomic scale than without them. [25][26][27][28][29][30][31][32][33] Some results have shown that the presence of aqueous solution has a great impact on mechanisms and energetics of surface reactions.…”
mentioning
confidence: 99%
“…For example, in acidic media, the Pt(110) surface can effectively catalyze CC bond cleavage, while the Pt(111) surface is almost inert. [ 15–17 ] Apart from (110) surface, alloying or doping Pt with other suitable metals to form Pt‐based nanocatalysts is an actionable strategy to enhance C1 pathway selectivity for EOR. [ 18–21 ] Among various Pt‐based nanocatalysts for the EOR, Pt–Ir nanocatalysts or nanocatalysts with Pt–Ir surface have attracted attention due to their remarkable advantages in C1 pathway selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical reduction of CO 2 into useful and stable chemical fuels represents a promising approach and attracts significant attention to mitigate CO 2 emissions in the atmosphere by supplying renewable electricity that generated from hydropower, wind, and solar. Among a series of metals that can electrochemically reduce CO 2 , Cu electrodes have unique ability to electro-reduce CO 2 into hydrocarbons, such as CH 4 and C 2 H 4 . Moreover, early experimental and theoretical investigations had reached consensus on the existence of a crucial intermediate CO adsorbed on the Cu surface during CO 2 electroreduction. , However, a high overpotential of ca. 1.0 V for a significant current density and low selectivity toward a particular species, such as CO, limited its application. Because of unique electrocatalytic ability of Cu electrodes, it is usually used to determine and validate CO 2 electroreduction mechanisms to seek new Cu-based alloy electrocatalysts in a more efficient way that can lower overpotentials and improve the selectivity of CO against its competitors, formate (HCOO – ) species and H 2 . Thus, CO 2 electroreduction mechanisms on the Cu surface have been extensively investigated by using experimental and theoretical methodologies. …”
Section: Introductionmentioning
confidence: 99%
“…However, theoretically studying the electrocatalytic mechanisms occurring at the electrode/aqueous interfaces is a challenging task because the considerations of solvation and electrode potential are required. Previously, the vacuum/solid interfacial model or the fixed H 2 O molecules were usually employed for the investigations of CO 2 reduction mechanism on the Cu electrodes in many theoretical calculations to reduce computational cost, leading to be not very convincing results. , To more realistically simulate the electrode/aqueous interfaces, some theoretical methods have been proposed. For example, ab initio molecular dynamics simulations (AIMD) may be able to describe the dynamic nature of H 2 O molecules and provide atomic insights into the mechanisms of CO 2 electroreduction into CO on Cu(100). Using the AIMD simulations model and an aqueous interfacial model with explicit H 2 O molecules, electrical field effects from solvated proton–electron transfer have been showed to play an important role in C–O bond breaking and CO formation mechanism. , The electroreduction pathways to CO and HCOO – species on Cu(100) were also examined by Goddard et al using AIMD simulation with an explicit description of H 2 O molecules . They concluded that chemisorbed CO 2 δ− can be an intermediate in forming CO with the conversion from CO 2 δ− to physisorbate CO 2 as the rate-determining step, while HCOO – species formation proceeded via a different route with surface-adsorbed H reacting directly with the physisorbate CO 2 .…”
Section: Introductionmentioning
confidence: 99%